Jacob Ten Eyck and Elizabeth Peebles indenture - Ten Eyck, Jacob C.; Peebles, Elizabeth
Indenture (1793 August 13) between Jacob Ten Eyck and Elizabeth Peebles for sale of land in Saratoga County, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Deeds -- New York (State) -- Saratoga County